Thoracic aorta traumatism.: Diagnostic and therapeutic aspects. - Filgueiras, José L; Ruso, Luis; Lorenzo, Alvaro; Estable, Héctor; Olivera, Daniel; Bergalli, Luis (Cirugía del Uruguay, 1988)
Three cases of traumatic rupture of the thoracic aorta operated o an emergency basis and two cases of post-traumatic aneurysms are presentad. The incidence, anatomic forms and behavior of this disease are analizad.